Physicochemical Studies of Some Properties of Drinking Water in Limited Sites of Babylon Governorate - Alhamdani, K.J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The physicochemical properties of drinking water in six different and limited sites on  Euphrates River in Babylon governorate were studied during the year of2004.Different parameters including (pH), alkalinity, turbidity, total hardness, magnesium, calcium, chloride and total dissolved solids in water were determined. It was found that the total hardness and the total dissolved solids were higher than those registered in the previous studies on TigrisRiver sites.Generally, the levels of these parameters were found to be within theallowed ranges of human uses, except the total hard:1ess.